2008
DOI: 10.2967/jnumed.108.055087
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Evaluation of18F-FDG and11C-Acetate PET/CT for Detection of Primary and Metastatic Hepatocellular Carcinoma

Abstract: Because 18 F-FDG PET has insufficient sensitivity for the detection of hepatocellular carcinoma (HCC), 11 C-acetate PET has been proposed as another technique for this use. We prospectively evaluated the value of PET/CT using these 2 tracers for the detection of primary and metastatic HCC. Methods: One hundred twelve patients (99 with HCC, 13 with cholangiocellular carcinoma) underwent biopsy and 18 F-FDG and 11 C-acetate PET/CT. Results: The overall sensitivities of 18 F-FDG, 11 C-acetate, and dual-tracer PET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
248
2
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(271 citation statements)
references
References 24 publications
11
248
2
10
Order By: Relevance
“…The observed uptake of a lipid tracer by cholangiocarcinoma is in accordance with the results of Park et al (25): a 69% (9/13) detection rate for 11 C-acetate versus 100% for 18 F-FDG. However, in a previous study, none of the 3 cholangiocarcinoma patients was 11 C-acetate PET-positive (17).…”
Section: Sensitivity For Liver Lesionssupporting
confidence: 91%
See 2 more Smart Citations
“…The observed uptake of a lipid tracer by cholangiocarcinoma is in accordance with the results of Park et al (25): a 69% (9/13) detection rate for 11 C-acetate versus 100% for 18 F-FDG. However, in a previous study, none of the 3 cholangiocarcinoma patients was 11 C-acetate PET-positive (17).…”
Section: Sensitivity For Liver Lesionssupporting
confidence: 91%
“…As we expected when designing the study, the diagnostic performance of 18 F-fluorocholine for the detection of intrahepatic HCC was close to published values for 11 C-acetate, with a sensitivity ranging from 75% to 87% (18,25). Using 11 C-choline PET and considering only foci with increased uptake as positive, Yamamoto et al (22) recently reported a lesion-based sensitivity of 63% only.…”
Section: Sensitivity For Liver Lesionssupporting
confidence: 80%
See 1 more Smart Citation
“…In fact, we have also published on the role of 18 F-FDG in the detection of poorly differentiated HCC and microvascular invasion for patients receiving a liver transplant. Patients with HCC tumors avid for 18 F-FDG have significantly less favorable overall survival and an increased chance of HCC recurrence (4).…”
Section: Replymentioning
confidence: 99%
“…FDG PET/CT has a low sensitivity in hepatic primary tumors (hepatocellular cancer), with radiotracers other than FDG showing better results [35]. No data on PET/MRI in this setting have been published so far; however, it is conceivable that combined PET/MRI, with the addition of fMRI, would perform as well as MRI alone.…”
Section: Whole-body Fdg Pet/mrimentioning
confidence: 99%